2009
DOI: 10.3233/jad-2009-0928
|View full text |Cite
|
Sign up to set email alerts
|

Balance Features in Alzheimer's Disease and Amnestic Mild Cognitive Impairment

Abstract: We evaluated alterations of balance by stabilometry in patients with amnestic mild cognitive impairment (aMCI) and with mild-moderate Alzheimer's disease (AD). Fifteen patients with aMCI and 15 with mild AD were recruited according to the current diagnostic criteria. Fifteen healthy subjects of the same age range were recruited as controls. Stabilometry was carried out using a commercial 4 load cell platform. Statistical analysis of between group differences was performed using one-way analysis of variance for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
78
2
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(90 citation statements)
references
References 28 publications
8
78
2
2
Order By: Relevance
“…Deterioration of physical performance became more evident with the decline in cognitive status from NCI to A-MCI, as previously reported [9,10,11]. However, our results further validated this pattern in the SCI population.…”
Section: Discussioncontrasting
confidence: 33%
See 1 more Smart Citation
“…Deterioration of physical performance became more evident with the decline in cognitive status from NCI to A-MCI, as previously reported [9,10,11]. However, our results further validated this pattern in the SCI population.…”
Section: Discussioncontrasting
confidence: 33%
“…Similarly, the physical performance of patients with SCI has not been investigated, although a growing number of previous studies have shown decreased physical performance in patients with A-MCI, MCI, and early AD [9,10,11,12]. Combining physical performance with cognitive performance data would provide a more comprehensive overview of functional features.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] Degradation of gait and balance was formerly thought to be a late sequelae of AD, but more recent evidence demonstrates these activity limitations early in the course of the disease. [13][14][15][16] Balance exercise programs have been shown to be effective in improving balance 17 and reducing falls 18 in older adults without cognitive defi cits but have not been well studied in IwAD.…”
Section: Introductionmentioning
confidence: 99%
“…Box 913, Dunedin, New Zealand; Tel: 0064 3 4795747; Fax: 0064 3 4799140; E-mail: paul.smith@stonebow.otago.ac.nz A number of studies have suggested that AD is associated with neurodegeneration of the vestibular system, which senses acceleration of the head and generates eye movement and postural reflexes to maintain visual acuity and balance during head movement. Patients with AD have been reported to exhibit deficits in the vestibulo-spinal reflexes [e.g., 21,22]. Furthermore, synaptic changes have been reported in the vestibulocerebellar systems of AD patients [23], as well as neurofibrillary tangles in the lateral vestibular nucleus [24], and the expression of beta-amyloid has been demonstrated in the vestibular nuclei of a mouse transgenic model of AD [25].…”
Section: Introductionmentioning
confidence: 99%
“…Since AD is associated with vestibular dysfunction [21,22], and vestibular dysfunction is associated with cognitive impairment [26][27][28][29][30][31][32][33][34][35][36][37][38], the main aim of this experiment was to use the cognitive deficits caused by vestibular dysfunction to test a putative nootropic drug that has been investigated as a possible treatment for AD [16]. To this end, rats subjected to bilateral vestibular lesions were tested in the 5CSRTT, to determine whether the ampakine, CX717 [7,9], could have any beneficial effect.…”
Section: Introductionmentioning
confidence: 99%